Angelic Troublemakers Religion and Anarchism in America - Wiley, A. Terrance (Contemporary Anarchist Studies, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Angelic Troublemakers is the first detailed account of what happens when religious ethics, political philosophy, and the anarchist spirit intermingle. Wiley deftly captures the ideals that inspired three revered heroes of nonviolent disobedience-Henry Thoreau, Dorothy Day, and Bayard Rustin. Resistance to slavery, empire, and capital is a way of life, a transnational tradition of thought and action. This book is a must read for anyone interested in religion, ethics, politics, or law.